2011
DOI: 10.1007/s00066-011-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective phase II trial of cetuximab plus VMAT-SIB in locally advanced head and neck squamous cell carcinoma

Abstract: The here reported toxicity data are promising and encouraging in regard to the adoption of moderate hypofractionation with VMAT-SIB techniques, when cetuximab is concomitantly administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Alongi et al reported 9% of grade 1, 36% of grade 2 and 45% of grade 3 mucositis in a series of 22 elderly and chemotherapy-ineligible patients treated with radiotherapy plus cetuximab [14]. The results obtained in our pilot study are similar, as 60% of patients had grade 1 to 2 mucositis, and 40% of patients had grade 3 to 4 mucositis.…”
Section: Discussionsupporting
confidence: 80%
“…Alongi et al reported 9% of grade 1, 36% of grade 2 and 45% of grade 3 mucositis in a series of 22 elderly and chemotherapy-ineligible patients treated with radiotherapy plus cetuximab [14]. The results obtained in our pilot study are similar, as 60% of patients had grade 1 to 2 mucositis, and 40% of patients had grade 3 to 4 mucositis.…”
Section: Discussionsupporting
confidence: 80%
“…9 In the era of dose painting intensity-modulated radiation therapy, it becomes crucial to spare healthy structures to improve the patient's quality of life. Volumetric modulated arc therapy (VMAT) has been evaluated for patients with head and neck cancer [10][11][12][13][14] showing that it is a fast, safe, and accurate technique.…”
Section: Introductionmentioning
confidence: 99%
“…3 Intensity-modulated radiation therapy (IMRT) and rotational intensity-modulated techniques, including volumetricmodulated arc therapy (VMAT), allow for a better dose conformation to target structures while reducing the dose. [4][5][6][7][8] In comparison with three-dimensional-conformal radiation therapy, several studies have shown that IMRT in HNC treatment reduces overall adverse effects such as xerostomia and dysphagia and thus improves QoL, even when chemotherapy is added. [9][10][11][12][13] Regarding tolerance of the parotid glands, several studies have suggested significant recovery when the mean dose is inferior to 26 Gy.…”
mentioning
confidence: 99%